1997
DOI: 10.1152/ajpendo.1997.272.6.e1008
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of nitric oxide synthase in the myometrium of the pregnant rat uterus

Abstract: Nitric oxide (NO) relaxes uterine smooth muscle and is produced by the pregnant uterus. Our previous studies revealed an increase in rat uterine NO synthase (NOS) activity in pregnancy and a decline at term. In the present study, we have examined the distribution of NOS isoform expression to determine whether their regulation is consistent with a role in the inhibition of uterine contractions before term. At day 17-18 of pregnancy, NOS immunohistochemistry revealed expression of two isoforms: endothelial const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 2 publications
2
28
2
Order By: Relevance
“…It has been reported that high levels of NO production in the myometrium during mid-gestation play a role in maintaining pregnancy by inhibiting uterine smooth muscle constriction, 16,17) and the findings of present study correlate well with these reports. In addition, the present study indicates that the decidua is a major region of uterine NO production.…”
Section: Resultssupporting
confidence: 91%
“…It has been reported that high levels of NO production in the myometrium during mid-gestation play a role in maintaining pregnancy by inhibiting uterine smooth muscle constriction, 16,17) and the findings of present study correlate well with these reports. In addition, the present study indicates that the decidua is a major region of uterine NO production.…”
Section: Resultssupporting
confidence: 91%
“…At a time when mRNA for the contractionassociated proteins was increasing, mRNA for iNOS decreased significantly. This pattern has been noted previously for iNOS protein in human (5) and rat (2,39). However, the current data are the first to temporally match the changes in iNOS with the other factors associated with uterine activation.…”
Section: Discussionsupporting
confidence: 87%
“…All three isoforms of NOS have been identified alone or in combination in the uterus of many species [1][2][3][4][5][6]. In general, at least one NOS isoform has been found in endometrial stroma, endometrial glands, decidua, decidual macrophages, vascular endothelial cells, and myometrial smooth muscle cells.…”
Section: Introductionmentioning
confidence: 99%